Quantification of β-Sitosterol by Validated High Performance Thin Layer Chromatography (HPTLC) Densitometric Method in the Flowering Buds of Mesua ferrea Linn (Journal of Scientific Research, 2023)
The medium-sized to large-sized tree Mesua ferrea Linn, commonly known as Nagakesara in India, can grow to be around 20 to 30 meters high and has incredibly durable wood. The fruiting season runs from January to March and April to October. The buds are globular, 2mm diagonally, and have scales in the axillary buds. It includes a significant amount of β-sitosterol amides, which are important from a biological perspective. In the current study, we used high-performance thin-layer chromatography (HPTLC) in association with densitometry to quantify these marker chemicals from Mesua ferrea Linn flowering buds. The technique was found to be accurate. For intra-day analysis, the relative standard deviation (RSD) values of β-sitosterol ranged from 1.16 to 1.60%, while for inter-day analyses, the values ranged from 0.68 to 1.77%. By performing a recovery study at three different levels for the standard chemicals, the accuracy of the approach was assessed, and average recoveries were determined to be 99.98%. It was observed that this TLC-densitometric approach was accurate, specific, particular, sensitive, and easy. For the simultaneous analysis of β-sitosterol from flowering buds of Mesua ferrea Linn, it can be employed in regular quality control.